Pengaruh Promosi, Rating Produk dan Kemudahan Penggunaan terhadap Minat Beli melalui Loyalitas Pelanggan sebagai variabel intervening pada aplikasi layanan pesan antar makanan Gofood : (Studi pada mahasiwa UPI YPTK Padang) - Zaki Fadlur Rahman; Vicky Brama Kumbara; Ai Elis Karlinda (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This research aims to find out how much influence promotions, product ratings and ease of use have on purchasing interest through customer loyalty to the Gofood food delivery service (study of UPI YPTK Padang students). The method used was accidental sampling, namely Gofood consumers among UPI YPTK Padang students. The research results showed that: there is an effect of promotion on customer loyalty, product ratings have a positive effect on customer loyalty, ease of use has no positive effect on customer loyalty, promotion has a positive effect on purchase interest, product ratings have no effect on purchase interest, ease of use has an effect on purchase interest, customer loyalty has a positive effect on purchase interest, promotion has a significant positive effect on purchase interest through customer loyalty, product ratings have a positive effect on purchase interest through customer loyalty, ease of use has no effect on purchase interest through Gofood customer loyalty among UPI YPTK Padang students.